Efficacy of Lactococcus lactis strain plasma (LC-Plasma) in easing symptoms in patients with mild COVID-19: protocol for an exploratory, multicentre, double-blinded, randomised controlled trial (PLATEAU study). Issue 9 (14th September 2022) - Yamamoto, Kazuko; Hosogaya, Naoki; Inoue, Tsuyoshi; Jounai, Kenta; Tsuji, Ryohei; Fujiwara, Daisuke; Yanagihara, Katsunori; Izumikawa, Koichi; Mukae, Hiroshi
Abstract : Introduction: The COVID-19 pandemic has been a major concern worldwide; however, easily accessible treatment options for patients with mild COVID-19 remain limited. Since the oral intake of Lactococcus lactis strain plasma (LC-Plasma) enhances both the innate and acquired immune systems through the activation of plasmacytoid dendritic cells (pDCs), we hypothesised that the oral intake of LC-Plasma could aid the relief or prevention of symptoms in patients with asymptomatic or mild COVID-19. Methods and analysis: This is an exploratory, multicentre, double-blinded, randomised, placebo-controlled trial. This study was initiated in December 2021 and concludes in April 2023. The planned number of enrolled subjects is 100 (50 subjects×2 groups); subject enrolment will be conducted until October 2022. Patients with asymptomatic or mild COVID-19 will be enrolled and randomly assigned in a 1:1 ratio to group A (oral intake of LC-Plasma-containing capsule, 200 mg/day, for 14 days) or group B (oral intake of placebo capsule, for 14 days). The primary endpoint is the change in subjective symptoms measured by the severity score. Secondary endpoints include SARS-CoV-2 viral loads, biomarkers for pDC activation, serum SARS-CoV-2-specific antibodies, serum cytokines, interferon and interferon-inducible antiviral effectors and the proportion of subjects with emergency room visits to medical institutions or who are hospitalised. Ethics and dissemination: The study protocol was approved by the Clinical Research Review Board of Nagasaki University, in accordance with the Clinical Trials Act of Japan. The study will be conducted in accordance with the Declaration of Helsinki, the Clinical Trials Act, and other current legal regulations in Japan. Written informed consent will be obtained from all the participants. The results of this study will be reported in journal publications. Trial registration number: Japan Registry of Clinical Trials (registration number: jRCTs071210097).